Biological Characteristics and Optical Reflectance Spectroscopy of Human Placenta Derived Mesenchymal Stem Cells for Application in Regenerative Medicine: Biological Characteristics and Optical Reflectance Spectroscopy of Placenta Mesenchymal Stem Cells - Zare, Sona; Ahmadi, Rahim; Mohammadnia, Abdolreza; Nilforoushzadeh, Mohammad Ali; Mahmoodi, Minoo (Journal of Lasers in Medical Sciences, 2021)
Introduction: The efficiency of stem cell isolation, culture, and biological characterization techniques for treatment is facing serious challenges. The purpose of this study was to provide a protocol for isolation and culture of three types of mesenchymal stem cells (MSCs) derived from the human placenta, amniotic membrane, and umbilical cord with high efficiency used for cell therapy. Methods: During this experimental laboratory study, 10 complete placenta samples were prepared from cesarean section mothers. The protocol for isolation and culture of mesenchymal cells from the placenta tissue, umbilical cord, and amniotic membrane was enzymatically optimized. The morphological features of mesenchymal cells were investigated using an inverted microscope and their biological features were measured using flow cytometry. The differentiation potential of the cells was evaluated by measuring their differentiation capacity into osteocytes and adipocytes. The absorption and reflectance features of the cells were recorded by optical spectroscopy. Finally, the data were statistically analyzed. Results: The expression of CD44, CD73, CD90, and CD29 markers in human placenta tissue-derived cells was significant. CD14, CD34, and CD45 markers were not expressed or were slightly expressed. These cells were highly viable and successfully differentiated into osteocytes and adipocytes. MSCs absorbed more light than visible light by showing light absorption peaks at wavelengths of about 435 and 550 nm. Conclusion: The protocol used in this study for isolation and culture of human placenta tissue-derived MSCs had significant efficiency for the production of MSCs for use in cell therapy and tissue engineering. DOI: 10.34172/jlms.2021.18